Study of the nature of special points in the phase plane of a student learning program discipline - Mokin, B. I.; Pyskliarova, A. V.; Mokina, Yu. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Using mathematical models, synthesized in a phase plane, the first stage of research of process of mastering the program of educational course by a student is carried out. The special points in the phase plane are defined, their character is evaluated and the semantic interpretation in terms of learning the discipline program by the student is shown in the paper.